2006
DOI: 10.1007/11908739_29
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Discretionary Access Control

Abstract: Abstract. A recent paper presented an access control scheme for discretionary access controls with a decidable safety problem. This paper deals with the complexity analysis of that access control, and finds it to be, in its worst cases, PSPACE-complete, but polynomial time for practical cases. The PSPACE-hardness reduction uses the theory of succinct problems in a more general manner than circuit representation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Each service provider provides different plans to access the services and packages. 1 SP has two plans 1 R and 2 R , 2 SP has only one plan 3 R . Each plan is considered as a role in the system.…”
Section: Permissions Conflicts In Prbacmentioning
confidence: 99%
See 1 more Smart Citation
“…Each service provider provides different plans to access the services and packages. 1 SP has two plans 1 R and 2 R , 2 SP has only one plan 3 R . Each plan is considered as a role in the system.…”
Section: Permissions Conflicts In Prbacmentioning
confidence: 99%
“…In traditional approaches, Discretionary Access Control [1] and Mandatory Access Control [2] were the only two possible access control models. In 1992, NIST found that these access control models are not always suitable to many organizations [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature on access control methods. A study related to DAC was presented in [44] regarding its complexity, safety, and issues in object-oriented databases. RBAC was widely studied as well, and researchers in [45] proposed object sensitive role assignment, which is a generalized RBAC model for object-oriented languages.…”
Section: Related Work On Access Controlmentioning
confidence: 99%
“…Another unique charecteristics of access control mechanism is to restore all the attempts being made the user to access the cloud resources for screen trust and building reputation. At present various access control schemes are-Discretionary Access Control (DAC) [41], Mandatory Access Control (MAC) [42]., and Role Based Access Control (RBAC) [43]. The generic architecture of existing access control over cloud is as shown below.…”
Section: Access Controlmentioning
confidence: 99%